Comparing the effects of current circumcision techniques on dorsal root ganglia: an experimental study - Ozgur Caglar; Remzi Arslan; Binali Firinci; Muhammed Enes Aydin; Erdem Karadeniz; Kemal Alp Nalci; Ahmet Bedii Salman; Mehmet Dumlu Aydin (Annals of Pediatric Surgery, 2021)
Abstract Background Circumcision is a surgical removal process of the preputium. Surgical excision and electric current cause neurodegeneration in the excised tissue-related neural network. This study investigates if circumcision and current surgical methods would cause histopathological changes in the penile tissue innervating pudendal nerve dorsal root ganglia. Results Vascular congestion occluded the microvessels, and degenerative changes were detected in postexcised penile tissue. Neuronal angulation, cytoplasmic condensation, nuclear shrinkage, and condensed nuclei were observed in the pudendal nerve ganglia. Moreover, the degenerated neuron (DN) densities of the pudendal nerve ganglia were 5 ± 2, 98 ± 22, 1093 ± 185, 236 ± 43 and 151 ± 19 in the control, the surgical circumcision, the monopolar cautery, the bipolar cautery and the thermocautery groups, respectively. Conclusions Although only the pudendal nerve endings are affected secondary to prepusium excision another pudendal axons can be damaged during bleeding control with cautery, the destruction of the neuron that sends this axon initiates a general inflammation in that ganglion. As a result, there may be a somatosensitive innervation defect in extrapenile tissues innervated by this ganglion. High-voltage electric devices should not be used unless obligatory.